2001
DOI: 10.1021/ja010181k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Homooligomers from Sugar Amino Acids:  Synthesis, Conformational Analysis, and Significance

Abstract: Sugar amino acids (SAAs) were designed as new building blocks carrying an amino group and a carboxyl group on a carbohydrate scaffold. By exploiting standard solid- and solution-phase coupling procedures, linear and cyclic homooligomers containing glucosyluronic acid methylamine (Gum) were synthesized. We achieved a high yield and a very short coupling time for the oligomerization and cyclization of sequences encompassing two, three, four, and six Gum units. The synthesis of cyclic oligomers containing only SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…The six-atom linker is suitable for use in solid-phase peptide synthesis, whilst the structural design of the building block contributes to the still expanding family of sugar amino acids (SAAs) [9][10][11] resembling conformationally restrained dipeptide isosters. [12][13][14][15][16][17] Members of this class of SAAs have found application in foldamers, [18,19] host-guest studies, [20] and as turn inducers. [21] We suggest SAA 12 as a promising candidate for such applications, due to the rigid nature of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The six-atom linker is suitable for use in solid-phase peptide synthesis, whilst the structural design of the building block contributes to the still expanding family of sugar amino acids (SAAs) [9][10][11] resembling conformationally restrained dipeptide isosters. [12][13][14][15][16][17] Members of this class of SAAs have found application in foldamers, [18,19] host-guest studies, [20] and as turn inducers. [21] We suggest SAA 12 as a promising candidate for such applications, due to the rigid nature of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 1 H NMR spectra before and after the addition of probe molecules may give further indication as to the type of interaction. 7 These results have given a basis for the investigation of related systems and future synthesis. …”
Section: Resultsmentioning
confidence: 93%
“…25 -27 The biological potential of these systems may be vast; Kessler et al have already identified a cyclic hexamer (of pyranose-based SAAs) which can form inclusion complexes with benzoic acid akin to the host -guest chemistry of cyclodextrins. 7 Cyclodextrins, cyclic sugars of (1!4)-linked a-D-glucopyranose units, have widespread use in drugs, foods, and cosmetics. 28,29 CPCDs 6,10,30 have been examined as part of an extensive project to investigate the structural features governing properties of both linear and cyclic carbopeptoids.…”
mentioning
confidence: 99%
“…Following the lead of PNAs (peptide nucleic acids), Goodnow et al 43,44 suggested the GNAs (glucopyranosyl nucleic amide) as oligomers of glucosamineuronic acid with nucleobases attached via a N-glycosidic linkage to the anomeric centers. In recent work, Kessler as well as Fleet have prepared a range of cyclic SAA macrolactams, [45][46][47][48] while Gregar and Gervay-Hague 49 have studied linear oligomers derived from amide-linked neuraminic acid analogues. For other examples of SAAs in carbopeptoids, see the comprehensive review on foldamers by Hill et al 50 …”
Section: Figurementioning
confidence: 99%